Historical Prerequisites for the Formation, Worldview, and Aesthetics of Romanticism: Specificity of the Ukrainian Model - Moskvichova, Yuliia; Mozgalova, Nataliia; Shcholokova, Olga; Baranovska, Iryna (Journal of History Culture and Art Research, 2019)
Romanticism is one of the most interesting phenomena in the history of the spiritual culture of mankind. The emergence of Romanticism in the late 18th - early 19th centuries is called "the romantic revolution in the art culture" by most researchers. The purpose of the study is to determine the socio-cultural prerequisites for the emergence of Romanticism as a global cultural movement. The basic philosophical traits of Romanticism and the theoretical concept of romantic art formed in the circle of German aesthetes are considered. The specificity of Ukrainian Romanticism is defined. The article proves that it is inextricably intertwined with the upholding of the Ukrainian national idea. The research is based on aesthetic-cultural, historical, comparative methods, and the method of system analysis. In terms of style, Romanticism is not only an artistic style but also a broad direction. It is based on the principle of freedom. Human personality with its individuality and uniqueness becomes the highest value. People are considered capable of creating new worlds and inspiring reality. A characteristic feature of the movement is the principle of universalism which combines art, philosophy, and science. Slavic Romanticism in many aspects is similar to Western European, but at the same time, it has pronounced national character and originality. The formation of the Romanticism in Ukraine has contributed to the awakening of national consciousness, the affirmation of cultural traditions, language, and literature. Ukrainian Romanticism is closely linked to the national liberation movement which has defined the themes and motives of this direction. The article systematizes the worldview of European and Ukrainian Romanticism, clarifies the key problems of romantic ethics and aesthetics. An attempt to reveal the conformity of nationally oriented ideas of Ukrainian Romanticism with the modern worldview and the idea of national consciousness of the Ukrainian society was made.